Clinical features and outcomes of young patients with epithelioid sarcoma: an analysis from the Children's Oncology Group and the European paediatric soft tissue Sarcoma Study Group prospective clinical trials. (May 2019) - Spunt, Sheri L.; Francotte, Nadine; De Salvo, Gian Luca; Chi, Yueh-Yun; Zanetti, Ilaria; Hayes–Jordan, Andrea; Kao, Simon C.; Orbach, Daniel; Brennan, Bernadette; Weiss, Aaron R.; van Noesel, Max M.; Million, Lynn; et al.
Abstract: Background: Data on the clinical features, optimal treatment and outcomes of paediatric patients with epithelioid sarcoma (ES) are limited and mostly retrospective. Methods: A subset analysis of ES patients < 30 years of age enrolled on two international prospective clinical trials conducted between 7/2005 and 11/2015 was performed. Risk-adapted therapy was based on tumour diameter, histologic grade, extent of surgery and presence/absence of metastases and included surgery ± radiotherapy for all patients with the addition of ifosfamide/doxorubicin chemotherapy for intermediate-/high-risk patients. Response to therapy, event-free and overall survival and pattern and predictors of treatment failure were evaluated. Results: Sixty-three ES patients (median age 13.1 years, 52% male) were eligible. Clinical features included the following: 68% extremity, median tumour diameter 3.5 cm, 56% high histologic grade, 14% nodal metastases, 14% distant metastases. Thirty-four low-risk patients underwent surgery (n = 30) or surgery/radiotherapy (n = 4); 16 intermediate-risk and 13 high-risk patients received chemotherapy ± surgery ± radiotherapy. Partial response was observed in 11/22 (50%) patients receiving neoadjuvant therapy. Events were local recurrence (n = 10) and distant recurrence (n = 15); estimated 5-year survival was 86.4%, 63.5% and 0%, respectively, for low-, intermediate- and high-risk patients. Locoregional nodal involvement, invasive tumour, high grade and lesser extent of resection predicted event-free survival in patients without metastases. Conclusions: Most low-risk ES patients who have undergone an adequate resection fare well without adjuvant therapy. Large tumour size, high histologic grade, tumour invasiveness, inadequate tumour resection and metastatic disease predict poorer outcomes in higher risk ES patients, for whom more effective therapies are needed. Clinical trial registration: COG ARST0332: ClinicalTrials.gov Identifier NCT00346164, EpSSG NRSTS 2005: European Union Drug Regulating Authorities Clinical Trials No. 2005-001139-31. Highlights: Large series of prospectively treated young patients with epithelioid sarcoma. Most low-risk patients treated with surgery alone fared well. Half of patients receiving neoadjuvant therapy had a partial tumour response. Poorer outcome predicted by large tumour size/invasiveness, high FNCLCC grade, metastatic disease and inadequate resection.